Grafting from Small Interfering Ribonucleic Acid (siRNA) as an Alternative Synthesis Route to siRNA–Polymer Conjugates - Lin, En-Wei; Maynard, Heather D (Macromolecules, 2015)
Small interfering ribonucleic acids (siRNAs) are important therapeutic agents and are challenging to deliver efficiently. To address this, covalent attachment of synthetic polymers to siRNA has become of great interest. In this report, we present a synthetic route to siRNA–polymer conjugates by the grafting from method, meaning that the polymerization of monomers occurs from an initiating site that is attached to siRNA. Specifically, a siRNA macroinitiator (siRNA-I) was prepared through disulfide exchange of 5′-thiol-modified siRNA with a pyridyl disulfide initiator. Activator generated by electron transfer atom transfer radical polymerization (AGET ATRP) of two monomers, poly(ethylene glycol) methyl ether methacrylate (PEGMA; M n = 300) and di(ethylene glycol) methyl ether methacrylate (DEGMA), was undertaken to synthesize a series of siRNA–polymer conjugates. The resulting conjugates were characterized by mass spectrometry and 1H nuclear magnetic resonance spectroscopy and compared to siRNA–pDEGMA conjugates prepared by the grafting to method in gel electrophoresis to estimate polymer molecular weight.